Influence of a Socially Assistive Robot on Physical Activity, Social Play Behavior, and Toy-Use Behaviors of Children in a Free Play Environment: A Within-Subjects Study - Raja Vora, Joseline; Helmi, Ameer; Zhan, Christine; Olivares, Eliora; Vu, Tina; Wilkey, Marie; Noregaard, Samantha; Fitter, Naomi T.; Logan, Samuel W. (Frontiers in Robotics and AI, 2021)
Background: Play is critical for children’s physical, cognitive, and social development. Technology-based toys like robots are especially of interest to children. This pilot study explores the affordances of the play area provided by developmentally appropriate toys and a mobile socially assistive robot (SAR). The objective of this study is to assess the role of the SAR on physical activity, play behavior, and toy-use behavior of children during free play. Methods: Six children (5 females, Mage = 3.6 ± 1.9 years) participated in the majority of our pilot study’s seven 30-minute-long weekly play sessions (4 baseline and 3 intervention). During baseline sessions, the SAR was powered off. During intervention sessions, the SAR was teleoperated to move in the play area and offered rewards of lights, sounds, and bubbles to children. Thirty-minute videos of the play sessions were annotated using a momentary time sampling observation system. Mean percentage of time spent in behaviors of interest in baseline and intervention sessions were calculated. Paired-Wilcoxon signed rank tests were conducted to assess differences between baseline and intervention sessions. Results: There was a significant increase in children’s standing (∼15%; Z = −2.09; p = 0.037) and a tendency for less time sitting (∼19%; Z = −1.89; p = 0.059) in the intervention phase as compared to the baseline phase. There was also a significant decrease (∼4.5%, Z = −2.70; p = 0.007) in peer interaction play and a tendency for greater (∼4.5%, Z = −1.89; p = 0.059) interaction with adults in the intervention phase as compared to the baseline phase. There was a significant increase in children’s interaction with the robot (∼11.5%, Z = −2.52; p = 0.012) in the intervention phase as compared to the baseline phase. Conclusion: These results may indicate that a mobile SAR provides affordances through rewards that elicit children’s interaction with the SAR and more time standing in free play. This pilot study lays a foundation for exploring the role of SARs in inclusive play environments for children with and without mobility disabilities in real-world settings like day-care centers and preschools.